650. ROBOTIC ESOPHAGEAL LEIOMYOMA ENUCLEATION. (24th September 2022) - Jiwnani, Sabita; Gopinath, Srinivas Kodaganur; Niyogi, Devayani; Tiwari, Virendra; Karimundackal, George; Pramesh, CS
Abstract: Leiomyomas are rare benign esophageal neoplasms. Surgery is indicated in symptomatic patients or if malignancy is suspected. A 20-year-old female presented with dysphagia to solids. Contrast enhanced computed tomography showed a 33-mm by 30-mm by 51 mm well circumscribed lobulated mass arising from the right anterolateral wall of the upper thoracic esophagus, causing luminal narrowing and abutting the azygos vein. An esophageal ultrasound performed for confirmation showed the lesion arising from the muscularis propria. Patient was scheduled for a robotic leiomyoma excision. Patient was placed in left lateral position, lung isolation was obtained with a double lumen tube. Four standard ports were placed in the sixth intercostal space. Robotic instruments used were the monopolar scissors, Maryland bipolar forceps, fenestrated bipolar forceps for dissection and needle holder for suturing. The leiomyoma was identified, mediastinal pleura and muscle layer were incised longitudinally. The leiomyoma was dissected all around in the submuscular plane taking care not to injure the underlying mucosa. However, while delivering the deep lobulated portion, there was an inadvertent injury to the mucosa. The mucosal tear was repaired with interrupted sutures utilising 4-0 Polydiaxanone sutures and the muscle layer was closed with V-Lock sutures. A check endoscopy was performed on table along with air insufflation with saline in the pleural cavity to check for an air leak. A nasogastric tube was placed, specimen was retrieved in a bag through the assistant port. Surgery was completed in 155 minutes with 50 ml blood loss. Post-operative course was uneventful, and the patient was discharged on full diet on the fourth post-operative day. Histopathology showed a SMA and desmin-positive spindle cell neoplasm without conspicuous mitotic activity. Precise dissection in a confined space is possible due to wrist-like movements, three-dimensional view and magnification offered by the robot. Repair of the injured mucosa and myotomy closure to prevent future diverticulum formation is easily accomplished with robotic suturing. Intraoperative endoscopy is useful in evaluating the integrity of the mucosa and muscle repair. Hence a robotic approach may be superior to a thoracoscopic/open leiomyoma enucleation and can be utilised even in moderate size masses.